Psychologism of E. Bronte’s Poetry (by Example of Poem “Remembrance” and Its Russian Translations) - O. G. Shevchenko (Научный диалог, 2018)
Significance and deep psychologism of one of Emily Bronte’s most famous poems “Remembrance” is considered. Attention is paid to the analysis of translations of this poem into Russian. The results of comparative analysis of two translations of this poem made by T. Gutina, famous translator of E. Bronte’s poetry, and Sh. Fenn, translator under the pseudonym, are presented. The question of relevance of the study of Emily Bronte’s poetry from the standpoint of psychoanalysis is raised. Special attention is paid to equivalence and adequacy in the translation of poetry. The key positions of the analysis of the translations of the poem by E. Bronte necessary for the transmission of the meaning of her poetry are determined. The novelty of the research lies in the fact that Emily Bronte, the author of the novel “Wuthering Heights,” well-known to Russian readers, is completely unknown for her poetry, which is rightfully worthy of attention of readers. The relevance of the research is due to the need to determine the basic key positions of the poetry translation, namely: preservation of the logical content, rhythmic and melodic pattern, stylistic expression when translating. The facts are given, urging that to pass the rhythm of a funeral march is fundamental for the poem “Remembrance”, and it was implemented in translators in full. The author focuses on the analysis of the system of images, as well as those formal characteristics of the poem, which contribute to the understanding of its deep meaning.